Diversity of Macroalgae in The Coastal Waters of Gunung Payung, Bali - Dewi, Ni Putu Swan; Dewi, Ayu Putu Wiweka Krisna; Pebriani, Dewa Ayu Angga (Department of Aquaculture, 2025)
Macroalgae are multicellular organisms that are part of algae with large or macro sizes and are classified as multicellular organisms. Gunung Payung Beach is a beach located in Kutuh Village, South Kuta District, Badung Regency, Bali. This beach has wave barriers in the form of coral reefs that serve as habitats for several types of macroalgae. This study aims to determine the diversity, coverage percentage, and importance value index of macroalgae in the waters of Gunung Payung Beach. The research was conducted from September to November 2023. The method used in this study is descriptive quantitative. The research location was divided into 3 stations, and the research was conducted using 1×1 m quadrat transects. Based on the research, a total of 47 species of macroalgae were found in the waters of Gunung Payung Beach. These macroalgae species came from 3 divisions: 13 species of Chlorophyta, 27 species of Rhodophyta, and 7 species of Phaeophyta. Ulva lactuca and Hypnea valentiae are macroalgae species with the highest coverage percentage at all stations. The calculation of the Shannon-Wiener diversity index shows that the diversity of macroalgae in the waters of Gunung Payung Beach is categorized as moderate, with values ranging from 1.948 to 2.916. The highest diversity index was found at station 2, which is 2.916. The highest macroalgae importance value index at all stations is Ulva lactuca. The growth of macroalgae is influenced by substrate factors and water quality. Gunung Payung Beach has suitable water conditions for the growth of macroalgae.